2012
DOI: 10.1164/rccm.201109-1666oc
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Inhaled Dry Powder Mannitol in Cystic Fibrosis

Abstract: Inhaled mannitol, 400 mg twice a day, resulted in improved lung function over 26 weeks, which was sustained after an additional 26 weeks of treatment. The safety profile was also acceptable, demonstrating the potential role for this chronic therapy for CF. Clinical trial registered with www.clinicaltrials.gov (NCT 00630812).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 24 publications
4
80
0
8
Order By: Relevance
“…It is difficult to compare results with those published in the literature since results are presented in terms of relative rather than absolute differences and sometimes with absolute changes in lung volume data rather than percent-predicted data. In two recent identical trials of mannitol in CF in which FEV 1 was expressed in the same way as in our trial (difference versus placebo in percent-predicted FEV 1 was 2.4%, 95% CI 0.9 to 3.9 in one trial [12] and 1.9%, 95% CI -0.02 to 3.8 in the other), changes were similar in magnitude to those demonstrated for tiotropium [13]. Treatment differences must also be considered in light of the study design and short duration of the trials.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is difficult to compare results with those published in the literature since results are presented in terms of relative rather than absolute differences and sometimes with absolute changes in lung volume data rather than percent-predicted data. In two recent identical trials of mannitol in CF in which FEV 1 was expressed in the same way as in our trial (difference versus placebo in percent-predicted FEV 1 was 2.4%, 95% CI 0.9 to 3.9 in one trial [12] and 1.9%, 95% CI -0.02 to 3.8 in the other), changes were similar in magnitude to those demonstrated for tiotropium [13]. Treatment differences must also be considered in light of the study design and short duration of the trials.…”
Section: Discussionsupporting
confidence: 80%
“…However, in the phase 3 trial, patients ≤11years in the placebo group showed an improvement in percent-predicted FEV 1 AUC 0-4h over time, which suggests a learning effect during the trial among the younger patients, who were less skilled in performing spirometry. In a recent study of inhaled mannitol, a sustained, significant (p<0.001) improvement in FEV 1 was seen in the control group [12], but the improvement was not significant in another similarly designed study (p=0.059) in similar populations [13]. Interestingly, in the pooled analysis, significant improvements in the mannitol versus control group in FEV 1 occurred in patients aged ≥18 years old but not in younger participants [14].…”
Section: Discussionmentioning
confidence: 93%
“…Although mannitol is currently used as stimulus in bronchial provocation tests (Figure 1), and thus may cause bronchoconstriction, BHR was reported in only two patients by Bilton et al [115] and was not observed by Aitken et al [116].…”
Section: Mannitolmentioning
confidence: 98%
“…This will increase the volume of the airway surface liquid and improves mucociliary clearance [115][116][117]. To date, two long-term trials (26 weeks) investigated the efficacy and safety of inhaled dry powder mannitol in CF patients [115,116] and a third long-term trial is running (NCT02134353).…”
Section: Mannitolmentioning
confidence: 99%
“…Prve raziskave o vplivu na pljučno funkcijo so bile obetavne, saj je manitol izboljšal FEV 1 za 7 % v primerjavi s placebom.34 Podobne zaključke je imela raziskava CF301.35 V nedavno objavljeni raziskavi (CF302) pa ugotavljajo relativno izboljšanje FEV 1 v skupini, ki je prejemala manitol v odmerku 2 × 400mg, le za 3,7 % v primerjavi s kontrolno skupino, ki pa je prejemala manitol v odmerku 2 × 50 mg. Med obema skupina ni bilo statistično pomembne razlike v številu poslabšanj. 36 Raziskovali so tudi učinek zmanjševanja aktivnosti natrijevih kanalčkov z amiloridom, tako bi zmanjšali absorbcijo natrija in vode iz površine dihalnih poti v epitelne celice ter preprečili izsuševanje sluzi na površini dihalnih poti. Metaanaliza petih randomiziranih s placebom kontroliranih raziskav o amiloridu ni pokazala izboljšanja pljučne funkcije ali čiščenja sluzi pri ljudeh s CF.37…”
Section: Izboljševanje Vlažnosti Sluzi V Dihalnih Potehunclassified